PERAN TRADISI SAMMAN DALAM MENGUKUHKAN KEAGAMAAN ISLAM RAHMATAN LIL’ALAMIN DI DESA ELLAK DAYA LENTENG SUMENEP - Syafiqurrahman Syafiqurrahman (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
Humans require both other humans and other creatures in order to survive. Humans are Zoon Politicon, which in Aristotle's terminology means social beings, including in the context of religious social life. As a result, the religious-social order that has been passed down from generation to generation is being undermined by Islamic da'wah ideas and groups that promote radicalization and extremism. During the Wali Songo era, Indonesia as a whole has had its own Islamic heritage and culture. The practice of Islamic traditions and culture in society, such as the samman tradition in Ellak Daya Lenteng Village, Sumenep, is one way to further develop Islam Rahmatan lil Alamin in people's life. The Sumenep people's religious nature is greatly influenced by the samman tradition, particularly in Ellak Daya Village. In this instance, samman can be seen as a tradition that embodies the religious community of Ellak Daya Village and embodies Islam rahmatan lil alamin. It is built on local wisdom and has a strong Islamic spirit. This study used a qualitative field method with a multi-case approach. The research resulted in a discussion of the implementation of the Kompolan Samman tradition in Ellak Daya Lenteng Village, Sumenep (Kompolan Samman Zikrul Ghafilin and Saiful Islam), and the role of the Kompolan Samman tradition in strengthening Rahmatan Lilalamin Islam in Ellak Daya Lenteng Village, Sumenep.